2015
DOI: 10.1590/1807-3107bor-2015.vol29.0065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a triclosan formula in controlling early subgingival biofilm formation: a randomized trial

Abstract: The aim of this study was to determine the efficacy of rinses with slurries of a dentifrice containing triclosan (TCS), as compared with rinses with slurries from a control dentifrice, in controlling early subgingival biofilm formation. A double-blind, randomized and cross-over clinical trial was designed, and 26 dental students were included. In the first period, participants were randomized to rinse with a TCS slurry or a control slurry, in a 12 h interval, and to refrain from mechanical cleaning. A Plaque F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…O objetivo dos agentes anti-biofilme e anti-gengivite é diminuir a inflamação gengival de modo que a doença periodontal destrutiva não se desenvolva ou tenha seu curso interrompido. Vários produtos anti-gengivite e anti-biofilme estão disponíveis comercialmente para os pacientes, e estes produtos são principalmente na forma de dentifrício ou enxaguatório bucal, onde a formulação adequada é importante tanto para manter a biodisponibilidade como para melhorar a substantividade (Andrade, Weidlich, Angst, Gomes & Oppermann, 2015). Alguns agentes estão adicionados nos dentifrícios com funções terapêuticas como anti-biofilme e anti-cálculo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O objetivo dos agentes anti-biofilme e anti-gengivite é diminuir a inflamação gengival de modo que a doença periodontal destrutiva não se desenvolva ou tenha seu curso interrompido. Vários produtos anti-gengivite e anti-biofilme estão disponíveis comercialmente para os pacientes, e estes produtos são principalmente na forma de dentifrício ou enxaguatório bucal, onde a formulação adequada é importante tanto para manter a biodisponibilidade como para melhorar a substantividade (Andrade, Weidlich, Angst, Gomes & Oppermann, 2015). Alguns agentes estão adicionados nos dentifrícios com funções terapêuticas como anti-biofilme e anti-cálculo.…”
Section: Discussionunclassified
“…O Triclosan (TRI) retarda o crescimento descendente de biofilme do ambiente supra para o subgengival, e tem a vantagem conhecida da adsorção e liberação de agentes químicos no meio oral (Andrade, Weidlich, Angst, Gomes & Oppermann, 2015). A metanálise feita por Gunsolley (2006) demonstrou que o copolímero gantrez é um elemento necessário para que o triclosan funcione de maneira adequada e com uma elevada substantividade Outro agente químico disponível no mercado é o Cloreto de Cetilpiridínio (CCP) que é um agente antimicrobiano (Miranda et al, 2020) e que tem propriedades catiônicas que ajudam a manter sua substantividade, o ensaio randomizado de Amini, Araujo, Mei-miau, Charles e Sharma (2009) utilizando um modelo experimental de gengivite apresentou redução no índice de biofilme quando utiliza-se CCP 2x por dia durante 2 semanas.…”
Section: Introductionunclassified
“…In children of aggressive periodontitis parents, a TRC toothpaste was demonstrated to be efficient in the management of the periodontal condition through the reduction of bleeding on probing, pocket depth, salivary Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ) and inflammatory markers [ 129 ]. This compound inhibits the subgingival biofilm formation and the overnight plaque [ 130 , 131 ], but its use has been controversial due to possible associations with low neonatal birth weight [ 132 , 133 ].…”
Section: Oral Antiseptics and Oral Conditionsmentioning
confidence: 99%
“…Maliska et al described an index to evaluate the presence of early subgingival biofilm formation, and found that an alcohol-containing 0.12% chlorhexidine solution reduced the number of dental surfaces bearing subgingival biofilm more than tenfold, compared with placebo 9 . The same index was used to demonstrate that triclosan could postpone early subgingival formation in the interdental area 10 . The potential of an alcohol-free chlorhexidine solution to prevent subgingival biofilm buildup has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%